Porfirinas de manganês não-simétricas: síntese, caracterização e emprego em catálise oxidativa - Vinícius Santos da Silva (2013)
This work describes the synthesis and characterization of non-symmetric porphyrins and metalloporphyrins, of which the 5,10-bis(4-aminophenyl)-15,20-diphenilporphyrinmanga-nese(III) chloride cis-MnIIIDAPDPPCl, 5,15-bis(4-amino-phenyl)-10,20-diphenylporphyrin-manganese(III) chloride trans-MnIIIDAPDPPCl and 5-(3-bromo-4-aminophenyl)-10,15,20-trisphenyl-2,3,7,8,12,13,17,18-octabromoporphyrin-manganese(III) chloride MnIIIBr9APTPPCl are new. The latter was obtained by direct -bromination of its analogue 5-aminophenyl-10,15,20-trisphenylporphyrin-manganese(III) chloride (MnIIIAPTPPCl). Regarding the electrochemical properties, the MnIIIBr9APTPPCl presented an anodic shift of its half-wave potential (centered on the metal ion, MnIIIP MnIIP) of 267 mV compared to the similar non-brominated (MnIIIAPTPPCl), being these systems classified as quasi-reversible. Studies of axial coordination to the metalloporphyrins MnIIIAPTPPCl and MnIIIBr9APTPPCl were performed with imidazole. In this study the formation constants for penta and hexacoordinate derivatives of those compounds were determined. MnIIIAPTPPCl exhibited log 1 = 1.95 and log 2 = 4.17 and MnIIIBr9APTPPCl exhibited log 1 = 4.58 and log 2 = 6.32. MnIIIBr9APTPPCl and MnIIIAPTPPCl were employed as catalysts in cyclohexane oxidation, using PhIO and PhI(OAc)2 as oxidant. The system MnIIIBr9APTPPCl/PhIO furnished the best cyclohexanol yields (C-ol = 40 %), with good selectivity (71 %) and higher resistance when compared with MnIIIAPTPPCl (C-ol = 22 % and selectivity = 60 %). Reactions were performed with the addition of imidazole (Im) and H2O, where the systems MnIIIAPTPPCl/PhIO/Im and MnIIIAPTPPCl/PhIO/H2O showed a significant increase in yield (~ 40%), selectivity for alcohol (~ 70% ) and recovery of the catalyst. Imidazole (Im) and H2O addition to the system MnIIIAPTPPCl/PhIO led to significantly higher yield (Col = 40%) and selectivity for the alcohol (70%). The addition of imidazole and H2O to the systems containing MnIIIBr9APTPPCl did not significantly alter product yields and selectivity when PhIO was used. The systems with PhI(OAc)2 showed lower yields when compared to those with PhIO. However when imidazole and H2O were added to the systems with PhI(OAc)2, there was a significant increase in the yield of oxidation products, but no significant changes in selectivity. Furthermore, it was observed the recovery of the -brominated catalyst from systems using PhI(OAc)2, a result without precedent in the literature.